EFFECT OF TURNING PARAMETERS OF AISI 316 STAINLESS STEEL ON TEMPERATURE AND CUTTING FORCES WITH FINITE ELEMENT MODEL - Unal, Engin; Karaca, Faruk (Vinca Inst Nuclear Sci, 2022)
Stainless steel materials are widely used in many industries today. Most of these materials are machined by turning. Modeling the temperature in the metal cutting process is a crucial step in understanding and analyzing the metal cutting process. However, when turning parameters are not chosen carefully, the integrity of the material deteriorates and the desired machining quality cannot be achieved. In this study, the effects of turning parameters on cutting temperature and force were investigated. Cutting speed, feed rate, and depth of cut were used as variable parameters for temperature and force analysis. Numerical analyzes were performed in ANSYS Workbench in accordance with the boundary conditions. Therefore, temperature distribution and cutting force were evaluated. As the control parameters increase, both the temperature and the cutting force increase. As a result, it can be considered that AISI 316 is the best choice for stainless steel alloy, since the minimum cutting speed, feed rate and minimum depth of cut conditions reduce the temperature formed in the cutting tool.
Keywords: AISI 316 stainless steel; cutting force; cutting temperature; finite element method; machining